Steganography Using Reversible Texture Synthesis - SenthilMurugan, J; Hariharan, G; Kirubagaran, R (International Journal of Computer Sciences and Engineering, 2025)
We suggest a new way as steganography applying a convertible framework combination. A convertible framework method examine a shorter convertible figure, whichever combine a current convertible figure along a same limited presentation also an approximate area. We unite the framework combination method into steganography to hide unseen information. In opposition to applying an extant mask figure to conceal information, our invention hide the authority framework figure also merge the hidden information completed the procedure of convertible framework. This permits us to passage the convertible information and authority framework againsta steganography authority framework. Our ways suggest three explicit benefits. First, our method suggests the merging sufficiency that is equivalent to the region of the steganography framework figure. Second, a steganalytic invention is not probable to beat our steganographic method. Third, the convertible facility ingrained against our scenario gives performance, whichever admit improving of the authority framework. Exploratory creature have confirmed that our advanced invention can give different characters of merging accommodation, give a optically reasonable framework figure, also reclaim theconnected combination.